2015
DOI: 10.1007/s12253-015-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation: an Avenue to Target Cancer Cells

Abstract: Tumorigenesis and metastasis are frequently associated with altered structure and expression of oligosaccharides on cell surface glycoproteins and glycolipids. The expression of sialylated glycoconjugates has been shown to change during development, differentiation, disease and oncogenic transformation. Abnormal sialylation in cancer cell is a distinctive feature associated with malignant properties including invasiveness and metastatic potential. The alterations in sialylation is accompanied by changes in sia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 34 publications
1
56
0
1
Order By: Relevance
“…Gangliosides are acid glycosphingolipids that carry one or more residues of sialic acid, and are more abundant in the brain [127, 130]. Sialin, a gene for sialic acid transporter, is upregulated in colon cancer CaCo-2M cells and breast cancer ZR-75-1 cells submitted to hypoxic conditions, and is related to enhanced gangliosides carrying N-glycolyl sialic acid (NeuGc) [131].…”
Section: Hypoxia Changes Membrane Glycoconjugates In Tumor Cellsmentioning
confidence: 99%
“…Gangliosides are acid glycosphingolipids that carry one or more residues of sialic acid, and are more abundant in the brain [127, 130]. Sialin, a gene for sialic acid transporter, is upregulated in colon cancer CaCo-2M cells and breast cancer ZR-75-1 cells submitted to hypoxic conditions, and is related to enhanced gangliosides carrying N-glycolyl sialic acid (NeuGc) [131].…”
Section: Hypoxia Changes Membrane Glycoconjugates In Tumor Cellsmentioning
confidence: 99%
“…Although not included in the original and next generation hallmarks, aberrant glycosylation is now also widely recognised as a new hallmark of cancer causally associated with all of the hallmark capabilities (2,3,6). One of the most widely occurring cancer associated changes in glycosylation is abnormal sialylation, which is often driven by the altered expression of sialyltranserase enzymes (7)(8)(9) and is linked to poor patient prognosis and metastasis (10)(11)(12)(13). Several sialyltransferase enzymes are implicated in cancer, but in recent years ST6GAL1 (which catalyses the addition of α2,6-linked sialic acids onto terminal N-glycans) has become increasingly dominant in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of cell membrane protein sialylation is often involved in the development of cancer and tumor metastasis (Pinho and Reis, 2015; Vajaria et al, 2015). Using specific lectin SNA, we found that UT-B1 from bladder cancer has defective alpha-2,6-sialylation.…”
Section: Discussionmentioning
confidence: 99%